ANALISIS PROFITABILITAS AGROINDUSTRI GULA SEMUT DI DESA AIR MELES ATAS KECAMATAN SELUPU REJANG KABUPATEN REJANG LEBONG - Putri Milanda Bainamus; Dwita Prisdinawati (University of Prof. Dr. Hazairin, SH, 2019)
The area of ??Rejang Lebong Regency in Selupu Rejang District is the business of the sugar palm business called UD Sari Aren. Granular palm sugar processing business has been running for more than fifteen years. Because UD Sari Aren is the only sugar granular palm industry the researchers are interested in seeing business feasibility through a profitability approach which is a comparison between earnings and capital. This study aims to determine the value of profitability and profit of UD Sari Aren granular palm sugar. This research uses census method, and profitability ratio analysis tool. Purposive sampling technique, with the criteria for one of the businesses that has been in existence for more than twelve years. The results of the study, the production costs incurred by UD. Sari Aren amounted to Rp 2,550,000,000 per year. The production value of this business is IDR 3,360,000,000 / year with a production of 96,000 kg / year. The selling price is IDR 35,000 / kg. the profit obtained is Rp. 810,000,000.- / year. The profitability value from the ratio of profit and capital is 31.76 percent. It can be interpreted that the business gets a profit far greater than the prevailing interest rate which is 18 percent per year Keywords: granular palm sugar, value of production, capital, profit, profitability